2015
DOI: 10.1016/j.neurobiolaging.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on glutamate neurotransmission in the substantia nigra of Gdnf heterozygous mice

Abstract: Glial cell line-derived neurotrophic factor (GDNF) helps protect dopaminergic neurons in the nigrostriatal tract. Although the cause of nigrostriatal degeneration is unknown, one theory is that excess glutamate from the subthalamic nucleus (STN) results in excitotoxic events in the substantia nigra (SN). Since dopaminergic degeneration is accompanied by a reduction in GDNF, we examined glutamate neurotransmission in the SN using a Gdnf heterozygous mouse model (Gdnf+/−) at 8 and 12 months of age. At 8 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…Initially, we looked at KCl-stimulated glutamate release in the dorsal striatum of MitoPark mice at 28 weeks of age, an age previously shown to develop LID in these mice (Shan et al, 2015). Glutamate release was measured by the amplitude of the electrochemical peak produced in response to pressure ejected 70 mM KCl (Farrand et al, 2015) which was applied locally in the dorsal striatum (Fig. 2B (dotted arrows) & 2C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we looked at KCl-stimulated glutamate release in the dorsal striatum of MitoPark mice at 28 weeks of age, an age previously shown to develop LID in these mice (Shan et al, 2015). Glutamate release was measured by the amplitude of the electrochemical peak produced in response to pressure ejected 70 mM KCl (Farrand et al, 2015) which was applied locally in the dorsal striatum (Fig. 2B (dotted arrows) & 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we assessed the kinetics of glutamate uptake as it has been previously reported that excess glutamate in the synaptic cleft can result in excitotoxic events as a result of over-activation of post-synaptic receptors leading to cell death (Misonou et al, 2006). In this study we examined glutamate uptake by measuring k −1 (sec −1 ), a constant of the decay of glutamate clearance signals (Farrand et al, 2015). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[95] suggest that reduced levels of GDNF induce excess glutamate release and deregulation of glutamate transporter-1, causing excitotoxicity in the nervous system that precedes dopaminergic degeneration. In this sense, a study performed by [96], showed GDNF expression level was increased with age in the frontal cortex, but was not in the hippocampus, in the agedependent changes in LC noradrenergic innervations suggesting that these innervations may be locally regulated by different neurotrophic factors that exert their trophic actions at different target sites.…”
Section: Gdnf and Agingmentioning
confidence: 99%
“…Notably, both of these neurotrophins modulate the activity of glutamatergic neurotransmission, which includes neuronal synaptic release and astrocytic glutamate uptake transporters activity/expression19, 20, while BDNF specifically modulates the expression of the high‐affinity monocarboxylate transporters 2 (MCT2) in neurons 21. The MCT2 controls the influx of energetic substrates including lactate to the oxidative metabolism in neurons 21.…”
Section: Introductionmentioning
confidence: 99%